Optimization of the composition and technology of the combined drug in the form of tablets for the treatment of hypertension - Sidenko, Larysa; Kazarinov, Mycola; Chub, Larisa; Almakaeva, Ludmila (Annals of Mechnikov's Institute, 2021)
Introduction. Cardiovascular diseases are the leading cause of death worldwide, including in Ukraine. A significant percentage of deaths are the result of pathologies associated with hypertension. In therapeutic practice of treatment of arterial hypertension the necessity of use of fixed combinations on the basis of amlodipine and bisoprolol is substantiated. In combination, these agents show an additive effect because they have different and complementary mechanisms of lowering blood pressure. This combination potentiates the antihypertensive and antiischemic effects. Material and methods. The objects of the study were API substances: amlodipine besylate produced by «Gloham Industries Private Limited», India; bisoprolol fumarate produced by «MOEHS CATALANA SL», Spain, the quality of which meets the requirements of the European Pharmacopoeia and the manufacturer's documentation, tablets and tablets obtained on their basis, as well as excipients: Prosolv HD 90 («JRS Pharma», Germany), crospovidone XL-10 («ISP Global Technologies», USA), magnesium stearate («FACI», Spain), calcium hydrogen phosphate anhydrous C92-22 («Budenheim», Germany), microcrystalline cellulose («Blanver Farmoquimica LTDA», Brazil), croscarmellose sodium («Mingtai Chemical Co. LTD», Taiwan), sodium starch glycolate («ISP Global Technologies», USA), PEO 6000 («Dow Chemical», Germany), talc («EVONIK», Germany). The study of 3 qualitative factors was performed using one of the plans of analysis of variance, in particular 3×3 Latin square. A complete factorial experiment of type 23 was used to study the three quantitative factors. The quality of the obtained tablets was evaluated by indicators: appearance, average weight, homogeneity of tablet weight, disintegration, dissolution, resistance to crushing, accompanying impurities, quantitative content. To assess the quality of the drug used methods: visual, gravimetric, liquid chromatography. Results and discussion. The study of pharmaco-technological properties of active substances showed that the substances have unsatisfactory volume characteristics. According to the calculated Carr index and Hausner coefficient, amlodipine besylate belongs to the "unsatisfactory" flow scale, and bisoprolol fumarate - "poor". Confirmation of this is the high value of the angle of natural slope. The results of research indicate the unsuitability of the properties of these substances to obtain tablets by direct compression. But since the percentage of total active substances is 5.25%: 3.86% - amlodipine besylate and 1.39% - bisoprolol fumarate, the properties of the tablet mass can be adjusted by excipients used for direct compression. Using the mathematical planning of the experiment and multivariate analysis of variance, the choice of the qualitative composition of the drug in the form of tablets. The research used mathematical planning of the experiment according to the scheme of 3×3 Latin square and studied the effect of 9 excipients used by domestic and foreign pharmaceutical manufacturers in the creation of tablets. According to the results of the studies, the most optimal excipients for the development of the composition of the drug in the form of tablets were selected: prosolv HD 90 as a filler, crospovidone as a superdisintegrant and magnesium stearate as a lubricant. Studies on the study of quantitative factors using a complete factor experiment 23 showed that when the average weight of the tablets (x3), at the lower level, the abrasion of the tablets was less than at the top. It is inexpedient to reduce the average weight less, so the factor x3 was stabilized at the lower level - 0.18 g. For other factors: it was decided as follows: the amount of crospovidone to leave at the upper level - 3% of the average weight, drug in production on the totality of all pharmaco-technological parameters of tablets and taking into account their geometric dimensions. When choosing the optimal technological scheme of tablet production, the physico-chemical and technological properties of active and auxiliary substances are taken into account. To prevent inhomogeneous mixing, as well as given that the drug has a low dosage of active substances, it was decided to develop a trituration method of introducing drugs into the tablet. Carried out studies of physicochemical compatibility, which was carried out by the accelerated method on the prepared model mixtures of amlodipine besylate and bisoprolol fumarate in doses and ratios of equivalent drug showed that no mixture showed changes in the characteristics and accumulation of by-products (decomposition products) during 6 months t =40°C and relative humidity of 75%. Conclusion. Using the method of mathematical planning, the qualitative and quantitative effect of excipients on the pharmaco-technological properties of the mass for tablets and tablets was investigated. It was found that the use of prosolv ND 90, crospovidone XL and magnesium stearate allows to obtain tablets containing amlodipine and bisoprolol, direct compression with indicators that meet the requirements of the State Pharmacopoeia of Ukraine. Using the method of accelerated storage, the absence of chemical modification of API in their joint presence and compatibility of API with excipients is shown. To prevent inhomogeneous mixing, a trituration method of introducing drugs into the tablet has been developed. Keywords: hypertension, tablets, amlodipine besylate, bisoprolol fumarate, pharmaco-technological indicators. DOI: 10.5281/zenodo.5761370